Customized Short-Form Social Media Grammar Videos on Grammatical Competence of Grade 8 Learners - Danibeth P. Allaba; Shienna Marie L. Caparas (International Journal on Integrated Education, 2026)
This study determined the effect of short-form social media grammar videos on the grammatical competence of Grade 8 learners at Southville 1 National High School during School Year 2025–2026. Anchored on the Comprehensible Input Hypothesis, Cognitive Load Theory, and Mastery Learning Theory, the study employed a quasi-experimental one-group pretest-posttest design. Thirty Grade 8 learners whose pretest scores were closest to the mean were purposively selected as respondents. A researcher-developed 30-item grammar test covering noun forms, subject-verb agreement, and word choice was used as the main instrument. Frequency, percentage, mean, Shapiro-Wilk test, and Wilcoxon Signed Rank Test were utilized in analyzing the data. Findings revealed that learners had generally fair pretest performance, particularly in noun forms and subject-verb agreement, while word choice was at an average level. After exposure to the short-form grammar videos, posttest results showed improvement in noun forms and subject-verb agreement, while word choice remained average. The test of significance further showed that there was a statistically significant difference between the pretest and posttest scores in noun forms and subject-verb agreement, leading to the rejection of the null hypothesis in these areas. However, no statistically significant difference was found in word choice. The study concluded that short-form social media grammar videos were effective in improving selected components of grammatical competence, particularly noun forms and subject-verb agreement, but were not sufficiently effective in significantly improving word choice.